Prácticas pedagógicas de enseñanza religiosa escolar en cuarto año de educación general básica en la unidad educativa Fe y Alegría de la ciudad de Guayaquil - Capelo Menéndez, Kattya Sayned (2016)
This paper is a case study, conducted in U. E. Fe y Alegría of the city of Guayaquil for three months. The study aims to determine the pedagogical practice in Religious Education (ERE) School. The study is based on observation two female teachers who teach the ERE in parallel A and B of the fourth year of basic general education school. For ethnographic research methodology, which involves the collection of data through the use of investigative tools such as interviews, observation of teachers in classes and the respective processing chips and field diary was used. The results contribute to the understanding of the aspects of pedagogical practice as planning, methodological issue of class structure, organization of work of the topic, using methodological resources, teacher-student interaction in activities, mastery of the subject and academic evaluation strategies used by teachers in the classroom. Importantly, the pedagogical practice of the ERE is developed based on the planning proposal for the guide books that teachers use. In analyzing the pedagogical knowledge of teachers where the importance of strengthening the training in the area of knowledge is valued note.